(untitled) (Revista de Ciências Agroveterinárias, 2021)
Weeds affect various crops worldwide, causing low yields and, therefore, significant economic losses. These losses can be minimized by the use of herbicides such as glyphosate. However, the efficiency of glyphosate depends on the type of agrochemical formulations. The most widely used surfactant is polyethoxylated tallow amine. Nevertheless, the disadvantage of these compounds is that their toxicity is greater than that of glyphosate itself. Thus, this study aimed to develop an environmentally-friendly combination of surfactants that can increase the performance of glyphosate compared to other currently used formulations. Saponin (S) is environmentally friendly and has a unique ability to go through the waxy cuticle of the weed leaf. However, its interfacial properties are very poor. In contrast, the alkyl glucoside (AG) mixture has shown excellent interfacial properties, being an environmentally safe surfactant, but cannot pass through the cuticle. In the present study, we mixed both surfactants. Two formulations were made with 20% (F1) and 2% (F2) of S with 4% AG. To verify the usefulness of our formulations, they were compared against a commercial product. The results showed that the commercial product had better CMC 0.3±0.1% and pC20 1.155±0.099 than our formulations F1 and F2. Formulations F1 and F2 showed better gCMC than the commercial product 36.5±4.1 mN/m and 30.9±1.4 mN/m, respectively. Field tests showed that F2 was more effective than the commercial product in eliminating weeds at the end of the test at 30 days. Our results allowed confirming that the use of saponin improves the efficiency of glyphosate. The work showed that structures similar to cyclopentaneperhydrophenanthrene are very effective for introducing drugs into plants through the leaves. This is an advance in general and in particular for the increase of the yield in certain crops.